Answer:
Final answer is 13.
Explanation:
Given expression is
-k+h+kh
We also have been given values of h and k as:
k=-5 h=-2
to simplify the given expression, we just need to plug the given values of k=-5 and h=-2 into -k+h+kh
-k+h+kh
![=-(-5)+(-2)+(-5)(-2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kzvldlhw4ueznluv0euc2avu8380yzcc7f.png)
![=5+(-2)+(-5)(-2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/l1v4qe4oxbuqtyno1jt7ni8ouhnnsmnacw.png)
![=5-2+(-5)(-2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/byyq1jecfcvors1qu9fq933d78b8g37ntx.png)
![=5-2+(10)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ul6gy820zg0ajqu8vfl7h7i9pcxwyv3aml.png)
![=5-2+10](https://img.qammunity.org/2020/formulas/mathematics/middle-school/at5qlc9yph4e7fbc17zsxcsseqaamu36p6.png)
![=3+10](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nb6escngzswok7qlrpw5ik4coqnvno3cq5.png)
![= 13](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2cu7l3e4u94gg5e319x7a7i928adkhtss3.png)
Hence final answer is 13.